2016
DOI: 10.18677/enciclopedia_biosfera_2016_140
|View full text |Cite
|
Sign up to set email alerts
|

Compactação, Densidade E Fertilidade Do Solo Na Área De Preservação Permanente Do Igarapé Dos Tanques – Porto Velho/Ro

Abstract: RESUMO Os solos das Áreas de Preservação Permanente-APP urbanas estão sob diferentes influências, o que pode levar a compactação. Nesse sentido foi realizado estudo na APP do Igarapé dos Tanques na cidade de Porto Velho-RO.Objetivouse com a realização deste estudo identificar a compactação do solo por meio da quantificação da resistência do solo à penetração-RP na APP da área de estudo e de investigar se esses resultados influenciam no crescimento das raízes. O levantamento foi conduzido nos dias 22/01/2016 e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The maps of georeferenced points in Area A and Area B are shown in Figure 3. Table 3 presents the results of root mean The results of soil density in Areas A and B are within the values determined for agricultural soils, which range from 0.9 to 1.8 g cm -3 , according to Pereira et al (2016). The correlations The UTM coordinates of the points measured by the GNSS devices employed, in the penetrometers, showed RMSE less than 3.50 m (Table 3).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The maps of georeferenced points in Area A and Area B are shown in Figure 3. Table 3 presents the results of root mean The results of soil density in Areas A and B are within the values determined for agricultural soils, which range from 0.9 to 1.8 g cm -3 , according to Pereira et al (2016). The correlations The UTM coordinates of the points measured by the GNSS devices employed, in the penetrometers, showed RMSE less than 3.50 m (Table 3).…”
Section: Resultssupporting
confidence: 69%
“…Clay content (Stefanoski et al, 2013) and type (Richart et al, 2005) interfere in soil resistance and resilience to compaction. Therefore, in more clayey soils, the loads on the surface act at greater depths, resulting in a thicker compacted layer of soil.…”
Section: Resultsmentioning
confidence: 99%
“…The clay, sand and silt fractions tend to be related to soil density so that sandy soil may have higher density than clay, whereas silt soil tends to have an intermediate behavior (LIBARDI, 2005). Pereira et al (2016) state that for clay soils the critical BD is between 1.30 and 1.40 g cm -3 , and between 1.40 and 1.50 g cm -3 and from 1.70 to 1.80 g cm -3 for medium-textured and sandy textured soils, respectively.…”
Section: Spatial Distribution Analysis Of Soil Physical Attributesmentioning
confidence: 96%
“…When considering the classification cited by Pereira et al (2016), some points of the brachiaria, orchard and andropogon subareas showed greater BD values than those considered critical and indicative of compaction, both at 0-10 and 10-20 cm depth (Figure 2 g, h). However, when analyzing the quantified values in the native forest subarea, BD values were also higher than those considered critical at both depths.…”
Section: Spatial Distribution Of the Soil Physical Attributes And Littermentioning
confidence: 99%